2016
DOI: 10.1080/02770903.2016.1196369
|View full text |Cite
|
Sign up to set email alerts
|

Asthma quality of life in Saudi Arabia: Gender differences

Abstract: Our findings revealed gender-specific differences in the correlates of AQL in Saudi Arabia, particularly in tobacco exposure, socio-economic factors and perceived asthma severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(21 reference statements)
0
3
0
1
Order By: Relevance
“…Most of the studies were conducted on pediatric subjects of less than 16 years of age [ 6 – 18 , 20 , 22 – 36 ] and 3 studies conducted on adults [ 19 , 21 ]. The studies enrolled school children as participants [ 6 – 20 ] and other studies were retrospective studies on asthma patients visiting hospital or PHC [ 21 – 36 ]. Sample sizes ranged from less than 150 to more than 10000, study settings were predominantly urban (27 studies), and 4 were mixed (both rural and urban) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies were conducted on pediatric subjects of less than 16 years of age [ 6 – 18 , 20 , 22 – 36 ] and 3 studies conducted on adults [ 19 , 21 ]. The studies enrolled school children as participants [ 6 – 20 ] and other studies were retrospective studies on asthma patients visiting hospital or PHC [ 21 – 36 ]. Sample sizes ranged from less than 150 to more than 10000, study settings were predominantly urban (27 studies), and 4 were mixed (both rural and urban) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, Moradi-Lakeh [ 19 ] in 2015 found no statistical difference between age and sex subgroups in the prevalence of asthma in their study. Torchyan [ 21 ], in a study exploring the effect of gender on asthma quality of life (AQL) with a score of 1 to 7, indicated a poor to better quality of life. The study reported a mean AQL of 4.3 and 4.0 for males and females, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asma dapat menyebabkan penurunan produktivitas kerja, gangguan pendidikan, penurunan kualitas hidup dan meningkatkan beban ekonomi (Sari, 2013). Pasien asma memiliki gejala sesak napas, bersin, nyeri dada, dan batuk yang dapat mempengaruhi kehidupan pasien asma (Mukherjee & Zhang, 2011;Torchyan et al, 2016). Gejala tersebut timbul karena peningkatan hiperesponsif jalan napas (Sari, 2013).…”
Section: Pembahasan Aunclassified